Going broad and deep: sequencing‐driven insights into plant physiology, evolution, and crop domestication. (6th January 2023) - Gui, Songtao; Martinez‐Rivas, Felix Juan; Wen, Weiwei; Meng, Minghui; Yan, Jianbing; Usadel, Björn; Fernie, Alisdair R.
SUMMARY: Deep sequencing is a term that has become embedded in the plant genomic literature in recent years and with good reason. A torrent of (largely) high‐quality genomic and transcriptomic data has been collected and most of this has been publicly released. Indeed, almost 1000 plant genomes have been reported (www.plabipd.de ) and the 2000 Plant Transcriptomes Project has long been completed. The EarthBioGenome project will dwarf even these milestones. That said, massive progress in understanding plant physiology, evolution, and crop domestication has been made by sequencing broadly (across a species) as well as deeply (within a single individual). We will outline the current state of the art in genome and transcriptome sequencing before we briefly review the most visible of these broad approaches, namely genome‐wide association and transcriptome‐wide association studies, as well as the compilation of pangenomes. This will include both (i) the most commonly used methods reliant on single nucleotide polymorphisms and short InDels and (ii) more recent examples which consider structural variants. We will subsequently present case studies exemplifying how their application has brought insight into either plant physiology or evolution and crop domestication. Finally, we will provide conclusions and an outlook as to the perspective for the extension of such approaches to different species, tissues, and biological processes. Significance Statement: This article reviews how sequencing technology has boosted pangenomics, promoted analysis of more complex genetic variations and single‐cell omics, and driven recent advances in studying plant physiology and evolution.